بقاء القناة الشريانية مفتوحة عند الخدج - سليمان سليمان; جوني عدي; حسن عبير صالح (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة (64) خديجاً قبلوا في قسم الأطفال في مشفى الأسد الجامعي في اللاذقية خلال الفترة من 1/8/2008 إلى 31/8/2009. هدف الدراسة تحديد نسبة بقاء القناة الشريانية مفتوحة (PDA) عند الخدج, حيث تم إجراء إيكو قلب وصورة شعاعية بسيطة للصدر لجميع الخدج. كانت نسبة بقاء القناة الشريانية مفتوحة (PDA) بعد اليوم الثالث من الحياة عند (64) خديجاً هي 26.56%. وكانت النسبة مرتبطة عكسياً مع زيادة العمر الحملي ووزن الولادة. This study included (64) preterms admitted to Pediatrics Department in Al-AssadAcademic Hospital during the period from 1/8/2008 to 31/8/2009. The aim of study was to determine the incidence of patent ductusarteriosus (PDA) in preterms. All patients have been exposed to Echo – cardiography and Chest – X – Rays. The incidence of patent ductusarteriosus beyond the third day of life in (64) preterms was 26.56% and was inversely related to increasedingestational age and birth weight.